MB-Isoster: um software para simulação de bioisosterismo - Elias, Thiago Castilho (2018)
In rational drug development field, bioisosterism is a tool to medicinal chemist who wants to improve their lead compounds performance, that is, bioisosterism refers to molecular fragment substitution by another that has similar physical chemistry properties. Thus, it is possible to modulate drug properties such as absorption, half-life increase and toxicity reduction. MB-Isoster software has been developed in order to help in rational drug design based on bioisosterism strategy. User starts with molecule of interest and selects molecular fragment to change, then, the software consults a database with bioisosteric relationship based on literature, and build new molecules. Generated bioisosteres can be filtered based on internally computed physical chemistry properties, such as logP and logS, in order to select molecules with appropriate pharmacokinetic properties. Another available function, to which it not needs to select a fragment, is substituting hydrogen atom in original molecule by a substituent among a set of 35 common organic radicals (methyl, hydroxyl, phenyl, and so on). A third function allows user to read receptor-ligand complex from a pdb file; non-bonded interactions (van der Waals and electrostatic) are computed between atoms from receptor and ligand, in order to indicate atoms in ligand with the highest energies as potential modification points. Lastly, it was installed a plugin that allows running virtual screening between bioisosteres and a receptor of interest using AutoDock Vina program as molecular docking engine. MB-Isoster is freely available at http://molmod-cs.unifal-mg.edu.br/tools. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.